Exploring multiculturalism in ‘The Weight of Our Sky’ by Hanna Alkaf among TESL pre-service teachers - Azlina Abdul Aziz,; Faiza Rostam Affendi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
One of the aspirations of the teaching of literature in English is to teach and promote ethics and values to students through literary texts by examining social cultural and political issues. In this study, we aim to examine the effectiveness of using ‘The Weight of Our Sky’ by Hanna Alkaf to interrogate multicultural issues. This novel is based on one of the darkest periods in Malaysian history, the 13th May 1969 racial riots. Since then, racial issues continue to be a concern and permeate our politics, culture, and social fabric. We examined interpretations of the text relating to multicultural issues of race and race relations by 48 Year 2 TESL student teachers from the Faculty of Education, UKM. This study employed a mixed methodology research, utilising questionnaire, and interview as instruments in collecting the data. The analysis of the data has yielded two main themes, a) the value of ‘TWOOS’ in terms of its i) multicultural values, lessons and conflicts, ii) multicultural themes, iii) multicultural characters, iv) multicultural settings, v) young adult related, and b) the relevance of TWOOS in discussing issues of multiculturalism. This study revealed the value of the novel by encouraging young adult readers to think deeply, be empathetic and be critical when discussing about the multicultural issues in our country.